Teori dan Praktek dalam Studi Konflik di Indonesia - Thung Ju Lan (Antropologi Indonesia, 2009)
Conflict studies are a social science field that identifies and analyses violent and nonviolent behaviors as well as the structural mechanisms attending social conflicts. This article seeks to analyze the methodology and conceptual problems in studying conflicts in Indonesia which is greatly influenced by Western social sciences tradition. The development of social sciences in Indonesia in describing conflict is supposed to be part of the root of Indonesian realities. However, Indonesian scholars lack of their own theoretical discourses which should have been developed by Indonesians to analyze conflict problems in the same level of understanding as if they were analyzed by Western perspective. As scientific discourses are socio-historical related, they go beyond than just ethic and emic principle in representing local perspective. The author also discusses conceptual misapprehension within Indonesian scholar regarding Modernist and Post-Modernist approach and research management Key words: Conflict studies, Scientific discourse, Methodology and Conceptual problems